2018
DOI: 10.1097/md.0000000000012582
|View full text |Cite
|
Sign up to set email alerts
|

The use of 5% lidocaine medicated plaster for acute postoperative pain after gynecological surgery

Abstract: Objectives:To examine the feasibility and potential efficacy of 5% lidocaine medicated plaster for acute postoperative pain in a parallel, blinded, randomized controlled pilot trial.Methods:Twenty-eight women undergoing elective gynecological surgery with midline incisions were randomly allocated 5% lidocaine medicated patch (Lignopad) or placebo plasters. Postoperative pain at rest and on movement at 24 hours were the primary study endpoints, with secondary endpoints of postoperative pain within the first 48 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…41 However, since that time, a small RCT was performed with 28 participants undergoing hysterectomy via planned vertical midline laparotomy incision, and this trial showed a nonstatistically significant trend in decreased cumulative MME usage; this group is planning a larger trial. 62 We did not find such a trend, but our population used a Pfannenstiel incision rather than a vertical midline incision, and in addition, the RCT on hysterectomy placed the patches directly adjacent to the incision. 62 At the start of our trial, there was 1 other trial investigating the use of lidocaine patches on postcesarean pain listed on Median pain scores overall and by prepregnancy and delivery BMI…”
Section: Original Researchmentioning
confidence: 82%
See 2 more Smart Citations
“…41 However, since that time, a small RCT was performed with 28 participants undergoing hysterectomy via planned vertical midline laparotomy incision, and this trial showed a nonstatistically significant trend in decreased cumulative MME usage; this group is planning a larger trial. 62 We did not find such a trend, but our population used a Pfannenstiel incision rather than a vertical midline incision, and in addition, the RCT on hysterectomy placed the patches directly adjacent to the incision. 62 At the start of our trial, there was 1 other trial investigating the use of lidocaine patches on postcesarean pain listed on Median pain scores overall and by prepregnancy and delivery BMI…”
Section: Original Researchmentioning
confidence: 82%
“…62 We did not find such a trend, but our population used a Pfannenstiel incision rather than a vertical midline incision, and in addition, the RCT on hysterectomy placed the patches directly adjacent to the incision. 62 At the start of our trial, there was 1 other trial investigating the use of lidocaine patches on postcesarean pain listed on Median pain scores overall and by prepregnancy and delivery BMI…”
Section: Original Researchmentioning
confidence: 82%
See 1 more Smart Citation
“…In a randomized controlled trial of 70 patients who underwent radical retropubic prostatectomy with a lower midline incision, a lidocaine patch was applied for 24 hours after the surgery, resulting in reduced pain scores and opioid consumption (13). A similar trial conducted on 28 patients who underwent open gynecological surgery with a midline incision found that postoperative pain reduced with lidocaine patch use (14).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been increasingly used in other neuropathic conditions [ 30 , 31 ] and many pain-related conditions due to its ease of use and low systemic adverse effects [ 32 , 33 ]. Several studies have supported that LP provide adequate postoperative pain relief after various surgeries, including laparoscopic appendectomy [ 34 ], gynecological surgery with midline incision [ 35 ], radical prostatectomy [ 36 ], and endoscopic discectomy [ 37 ]. LP are 10 ⅹ 14 cm sized hydrogel adhesive patches containing 700 mg of lidocaine at a 5% concentration.…”
Section: Topical Agentsmentioning
confidence: 99%